Compression-shear performance and failure criteria of seawater sea-sand engineered cementitious composites with polyethylene fibers. (22nd August 2022) - Liao, Qiao; Su, Yuanrui; Yu, Jiangtao; Yu, Kequan
Highlights: Tests on the compression-shear performance of seawater sea-sand ECC were performed. Seawater sea-sand ECC under the combined loading shows ductility failure mode and high shear strength. Failure law is reflected by the criterion based on octahedral stress or stress invariant. The failure criterion of seawater sea-sand ECC could be applied in future structural analysis. Abstract: Seawater sea-sand engineered cementitious composites (SS-ECC) with polyethylene (PE) fibers holds wide application prospects. However, the understanding on its mechanical behaviors and failure criteria under combined compression-shear loading, which is essential for structural application, is lacking. The object of this research is to obtain the mechanical performance and establish the corresponding failure criteria of SS-ECC under combined loading. The influences of fiber content and normal stress ratio on failure modes, shear strength, peak shear displacement and shear strength components were analyzed. SS-ECC under combined loading exhibited ductile failure mode. Shear strength increased significantly with the increasing normal stress ratio, while increased slightly with higher fiber content. The effects of fiber content and normal stress ratio on the combined compression-shear behaviors were clarified. Further, the failure criteria based on octahedral stress and stress invariant were proposed for describing the failure law of SS-ECC under combined loading. This research lays the groundwork for understanding the mechanical performance of SS-ECC under combined compression-shear loading and preparing its application in structural members.